Application of Mobile Technologies for the Formation of Analytical Competence of Future Specialists - Galustyan, Olga Vladimirovna; Smetannikov, Alexander Pavlovich; Kolbaya, Indira Grigoryevna; Palchikova, Galina Sergeevna; Galigorov, Denis Vasilyevich; Mazkina, Olga Borisovna (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The article deals with application of mobile technologies for the formation of analytical competence of future specialists. It discusses the concepts of mobile learning and mobile technologies. Advantages of using mobile technologies within the learning process are presented. The use of mobile learning is one of the most effective and affordable ways of formation of students' analytical competence. Managing, strategic, informational, reflexive components within the structure of analytical competence are revealed in the article. The results of experimental work of formation of analytical competence of future specialists by means of mobile learning technologies are presented. The authors conclude that formation analytical competence of future specialists using mobile devices expands the conventional framework by using the capabilities of mobile platforms and expands the learning environment.